2016
DOI: 10.1155/2016/9450137
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Salidroside in the MPTP Mouse Model of Parkinson’s Disease: Involvement of the PI3K/Akt/GSK3βPathway

Abstract: The degenerative loss through apoptosis of dopaminergic neurons in the substantia nigra pars compacta plays a primary role in the progression of Parkinson's disease (PD). Our in vitro experiments suggested that salidroside (Sal) could protect against 1-methyl-4-phenylpyridine-induced cell apoptosis in part by regulating the PI3K/Akt/GSK3β pathway. The current study aims to increase our understanding of the protective mechanisms of Sal in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropypridine- (MPTP-) induced PD mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…The Bcl‐2/Bax ratio is a determining factor in the regulation of apoptotic cell death (Bar‐Am et al, ). In present study, we also found that salidroside reverses MPP + ‐induced the up‐regulation of Bax/cl‐2 ratio, while this effect was blocked by sirtinol, which is consistent with the study done by Zhang et al () and the research done by Kou et al (). These results suggest that SIRT1 contributes to the neuroprotective effect of salidroside against PD in part through improving mitochondrial apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…The Bcl‐2/Bax ratio is a determining factor in the regulation of apoptotic cell death (Bar‐Am et al, ). In present study, we also found that salidroside reverses MPP + ‐induced the up‐regulation of Bax/cl‐2 ratio, while this effect was blocked by sirtinol, which is consistent with the study done by Zhang et al () and the research done by Kou et al (). These results suggest that SIRT1 contributes to the neuroprotective effect of salidroside against PD in part through improving mitochondrial apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that salidroside administration induced an additional increase in dopamine and reversed the reduction of both DOPAC and HVA. These results were similar to those reported recently, in which salidroside administration increased the levels of DA, DOPAC, and HVA in the striatum of brains with neurodegenerative disease (Zhang et al, 2016;Li and Chen, 2019). Under normal conditions, the dopaminergic system maintains a steady state; however, this fine balance is affected when any factor is disrupted and consequently induces serious physiological reactions (Defaix et al, 2018;Zeiler and Menon, 2018;Dyhrfort et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Degenerative alterations in the ipsilateral SNpc have also been reported in clinical patients with neurodegenerative disorders (Lou et al, 2009;Nakajima et al, 2010;Robles, 2016). Several studies have demonstrated that salidroside potentially targets extracellular TH secretion in the SNpc (Zhang et al, 2016;Wu et al, 2018;Li and Chen, 2019). Indeed, our data showed a similar observation: salidroside treatment prevented dopaminergic neurons loss as displayed by the preservation of TH-positive cells in the rat SNpc.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, abnormal regulation of GSK-3beta can lead to the pathophysiological manifestations of PD. Some studies have suggested that GSK-3beta is abnormally expressed in PD [94][95][96].…”
Section: Progress In Understanding the Role Of Pi3k/akt/mtor In Pdmentioning
confidence: 99%